Gender and Teaching: Focus on the professional development of teachers in rural areas of Brazil and Colombia - Diniz, Margareth; Lima Jardilino, José Rubens (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This work aims at discussing the women ́s topic of the teachers ́ development for rural school, based on the psychoanalysis the development problem located in the holder - the gender, the subject and teaching. The research was carried out in Brazil and Colombia, sometimes by different groups are trying to find in the presentation of women teacher ́s life stories as participants looking for the subjective meaning of being a woman and teacher in the rural areas. The surveyed teachers contributed their ideas, stories and glances in relation to the places where they live and work. They talk about their personal and professional paths and they present their views about the students / they and their families. The communities of every place that the research, let us say Tunja, in the department of Boyacá and Santa Rita de Ouro Preto, in the district of the historic town of Ouro Preto, Minas Gerais, Brazil.